Scholar, gentleman and player: a tribute to Eric Dunning. Issue 10 (11th September 2020) - Malcolm, Dominic; Waddington, Ivan
Abstract: This article provides a tribute to the life and career of Eric Dunning. It explores how Eric Dunning was one of the first people to recognize the potential of sport as a field of sociological study and how, in the 1960s, he was central in both the intellectual and organizational development of the emerging field. In the 1970s and 1980s Dunning collaborated on some key historical sociological research which enabled the field to consolidate, expand and exert some significant political influence in the UK in relation to the social issue of football hooliganism. It concludes with a review of some of the formal and informal recognition Dunning received from both sociological and historical scholars of sport, and notes that he will be much missed in both communities.